A new aberrant species of Nipponocercyon from the mountains of southeastern China (Coleoptera: Hydrophilidae: Sphaeridiinae) - Fikáček, Martin; Jia, Fenglong; Ryndevich, Sergey (Zootaxa, 2015)
Nipponocercyon satoi sp. nov. is described from the mountains of Zhenjiang and Jiangxi Provinces in Southwest China. Although the species bears all synapomorphies of Nipponocercyon Satô, 1963, it differs substantially from the other two species of the genus by its Pacrillum-like habitus (i.e. small, compact and strongly convex body with reduced surface sculpturing). The new species is compared in detail with the other two Nipponocercyon species as well as with Pacrillum Orchymont, 1941 and Megasternum Mulsant, 1844. The generic diagnosis of Nipponocercyon is adapted, and reasons for assigning the new species to Nipponocercyon are discussed.